2012
DOI: 10.1039/c2dt31527k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and in vitro inhibitory studies against human breast cancer of the bis-(2,6-di-tert-butylphenol)tin(iv) dichloride and its complexes

Abstract: Four new organotin(IV) complexes of bis-(2,6-di-tert-butylphenol)tin(IV) dichloride [(tert-Bu-)(2)(HO-Ph)](2)SnCl(2) (1) with the heterocyclic thioamides 2-mercapto-pyrimidine (PMTH), 2-mercapto-4-methyl-pyrimidine (MPMTH), 2-mercapto-pyridine (PYTH) and 2-mercapto-benzothiazole (MBZTH), of formulae {[(tert-Bu-)(2)(HO-Ph)](2)Sn(PMT)(2)} (2), {[(tert-Bu-)(2)(HO-Ph)](2)Sn(MPMT)(2)} (3), {[(tert-Bu-)(2)(HO-Ph)](2)SnCl(PYT)} (4) and {[(tert-Bu-)(2)(HO-Ph)](2)SnCl(MBZT)} (5), have been synthesized and characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 42 publications
0
32
0
5
Order By: Relevance
“…It is also observed that the complexes 1a and 1b showed moderate to high activities against Gram negative and Gram‐positive bacteria, respectively. An investigation of literature reveals that tin exhibits outstanding antibacterial property that would lead to biomedical applications . Besides, nano‐size compound 1b showed more antimicrobial activity than its bulk form 1a .…”
Section: Resultsmentioning
confidence: 99%
“…It is also observed that the complexes 1a and 1b showed moderate to high activities against Gram negative and Gram‐positive bacteria, respectively. An investigation of literature reveals that tin exhibits outstanding antibacterial property that would lead to biomedical applications . Besides, nano‐size compound 1b showed more antimicrobial activity than its bulk form 1a .…”
Section: Resultsmentioning
confidence: 99%
“… 4 8 In general, the biochemical activity of organotin compounds is influenced by the structure of the resulting compounds and the nature and number of organic groups bound to the tin center. 9 15 In addition, the choice of coordinated ligand is also imperative in the biological effects of organotin compounds, such as solubility and bioavailability. A judicious choice of coordinating ligand not only can minimize the drawbacks, but also can enhance or modulate the activity of organotin compounds, 16 as the ligand plays the key role in transporting and directing the molecule to the target site.…”
Section: Introductionmentioning
confidence: 99%
“…Tin complexes have witnessed vast range of applications in various biological and industrial fields . Such compounds possess fascinating medicinal importance like antiparasite agents, in horticulture as bactericidal, acraricidal and fungicidal medium, anti‐HIV and antitumor agents . The biological activity and specially the anticancer activity of tin compounds is governed by geometrical features, extent of hydrolysis of ligands and coordination number around central tin metal ion .…”
Section: Introductionmentioning
confidence: 99%